A checklist of land snails from the west coast islands of Sabah, Borneo (Mollusca, Gastropoda) - Chee, Chean Phung; Tuh, Fred Yit Yu; Thor, Seng Liew (Pensoft Publishers, 2017)
Sabah, situated in one of the world’s biodiversity hotspots, has the largest number of islands in Malaysia with more than 500 of various sizes and degrees of isolation. However, information on the islands’ biodiversity is limited. This study provides an up-to-date checklist of land snail species found on 24 west coast islands in Sabah. A total of 67 species (nearly 20% of the total number of land snail species in the state) representing 37 genera and 19 families is enumerated based on systematic field surveys of 133 sampling plots, BORNEENSIS database records and species checklists published between 2000 and 2016. The number of species on the islands ranges from four to 29. Labuan Island has the highest number of species (29), followed by Tiga Island (25), Mantanani Besar Island (24) and Gaya Island (23). However, the populations of some land snail species may have declined as several previously recorded species on the islands were not found in a recent systematic field sampling. This checklist is provided as a baseline inventory for future island land snail studies and to better inform biodiversity conservation plans of marine parks and other islands on the Sabah west coast.